The Effects of High-Rise Building on Urban Thermal Environments and Outdoor Thermal Comfort: A Case Study of Suburban Residential Development nearby the Rangsit Campus of Thammasat University - Prasitreak, Danaipat; Srivanit, Manat (Journal of Architectural/Planning Research and Studies (JARS), 2021)
Outdoor thermal comfort in urban spaces is an important indicator of the quality of life in urban environment, especially in tropical cities of Thailand. This paper attempts to investigate thermal comfort from the outdoor microclimate effects surrounded by residential buildings in the university campus town in Pathum Thani province, focusing on the effect of a high-rise building on urban thermal environments and outdoor thermal comfort. The micro-climatic conditions of pre-and post-construction scenarios were determined by the ENVI-met numerical simulation and the post-processing tool called BioMet, as a post-processing tool to calculate human thermal comfort indices. In this study, the Physiologically Equivalent Temperature (PET) was utilized as the thermal index to assess outdoor thermal comfort. It has been investigated quantitatively that the mean radiant temperature and wind velocity provided by high impact changes, which can affect outdoor thermal comfort in the pedestrian thermal environment around the tall building. Thus, it is recommended to improve pedestrian wind environment around tall buildings, to reduce radiant heat from the sun interacts with the ground surface materials and building envelope, and to create human thermal comfort outdoor.